Aspects of Linguistic Variation - Brisard, Frank; Mortelmans, Tanja; Olmen, Daniël (Trends in Linguistics. Studies and Monographs [TiLSM] ;, 2018)
Linguistic variation is a topic of ongoing interest to the field. Its description and its explanations continue to intrigue scholars from many different backgrounds. By taking a deliberately broad perspective on the matter, covering not only crosslinguistic and diachronic but also intralinguistic and interspeaker variation and examining phenomena ranging from negation over connectives to definite articles in well- and lesser-known languages, the volume furthers our understanding of variation in general. The papers offer new insights into, among other things, the theoretical notion of comparative concepts, the social or mental nature of language structure, the areal factor in lexical typology and the diachronic implications of semantic maps. The collection will thus be of relevance to typologists and historical linguists, as well as to people studying variation within the areas of cognitive and functional linguistics.